Attaining the age threshold for adolescent mental health services: factors associated with transition of care in the independent sector in Ireland. (11th March 2019) - Bond, L.; Feeney, A.; Collins, R.; Khurshid, I.; Healy, S.; Murtagh, A.; Power, P.
Abstract : Objectives: The transition from adolescent to adult mental health services (AMHS) is associated with disengagement, poor continuity of care and patient dissatisfaction. The aim of this retrospective and descriptive study was to describe the 'care pathways' in an independent mental health service when adolescents reach age 18 and to investigate the level of engagement of those who transitioned to independent AMHS. Methods: This is a retrospective, naturalistic and descriptive study in design. All patients discharged from the St Patrick's Adolescent Mental Health Service aged 17 years and 6 months and older, during a 3-year period between January 2014 and December 2016, were included. Electronic records were used to collect socio-demographic and clinical details and to determine engagement rates in adolescents who transferred to independent adult services. Results: A total of 180 patients aged over 17 years and 6 months were discharged from the adolescent service. Of these, 45.6% were discharged to their GP, 28.9% to public mental health services and 25.6% to independent mental health services. The majority who transitioned to independent AMHS went to a Young Adult Service, which had high engagement rates at 3 and 12 months post-transition. Conclusions: In this independent mental health service, less than half of adolescents who reach the transition age are referred onto AMHS. Engagement rates were found to be high among those referred on to a specialised young adult service.